Identification of miRNAs and associated pathways regulated by Leukemia Inhibitory Factor in trophoblastic cell lines. (December 2019) - Morales-Prieto, Diana M.; Barth, Emanuel; Murrieta-Coxca, Jose Martín; Favaro, Rodolfo R.; Gutiérrez-Samudio, Ruby N.; Chaiwangyen, Wittaya; Ospina-Prieto, Stephanie; Gruhn, Bernd; Schleußner, Ekkehard; Marz, Manja; Markert, Udo R.
Abstract: Introduction: Leukemia Inhibitory Factor (LIF) regulates behavior of trophoblast cells and their interaction with immune and endothelial cells. In vitro, trophoblast cell response to LIF may vary depending on the cell model. Reported differences in the miRNA profile of trophoblastic cells may be responsible for these observations. Therefore, miRNA expression was investigated in four trophoblastic cell lines under LIF stimulation followed by in silico analysis of altered miRNAs and their associated pathways. Methods: Low density TaqMan miRNA assays were used to quantify levels of 762 mature miRNAs under LIF stimulation in three choriocarcinoma-derived (JEG-3, ACH-3P and AC1-M59) and a trophoblast immortalized (HTR-8/SVneo) cell lines. Expression of selected miRNAs was confirmed in primary trophoblast cells and cell lines by qPCR. Targets and associated pathways of the differentially expressed miRNAs were inferred from the miRTarBase followed by a KEGG Pathway Enrichment Analysis. HTR-8/SVneo and JEG-3 cells were transfected with miR-21-mimics and expression of miR-21 targets was assessed by qPCR. Results: A similar number of miRNAs changed in each tested cell line upon LIF stimulation, however, low coincidence of individual miRNA species was observed and occurred more often among choriocarcinoma-derived cells (complete data set at http://www.ncbi.nlm.nih.gov/geo/ under GEO accession number GSE130489). Altered miRNAs were categorized into pathways involved in human diseases, cellular processes and signal transduction. Six cascades were identified as significantly enriched, including JAK/STAT and TGFB-SMAD. Upregulation of miR-21–3p was validated in all cell lines and primary cells and STAT3 was confirmed as its target. Discussion: Dissimilar miRNA responses may be involved in differences of LIF effects on trophoblastic cell lines. Highlights: LIF induces changes in the miRNA prolife of trophoblastic cells. Changes are most similar among different choriocarcinoma, but not HTR8/SVneo cells. Six cascades are significantly enriched, including JAK/STAT and TGFB-SMAD. miR-21–3p was upregulated in all cell lines upon stimulation with LIF. STAT3 and SMAD7 were identified as potential miR-21–3p targets.